Regulación fiscal para la elaboración de las declaraciones del impuesto de renta para personas naturales en Colombia y Chile (2015)
This paper describes fiscal policy for the preparation of income tax returns for individuals in Colombia and Chile, using as a technique for the development of work collecting information and a descriptive analysis. The paper explains every one of the tax items, tax systems, tax rates, purification systems and procedures for the clearance of the taxable base of income tax contained in the legislation of each country of a profound way, practice and allowing detailed understanding of the issues and failing to capture the reader's interest.